RESISTENSI TERHADAP NASIONALISME JEPANG:: TANGGAPAN KRISTEN TERHADAP GERAKAN AMANDEMEN DI JEPANG - Surya Harefa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
This article explores several responses of Japanese Evangelical Christians to Japanese nationalism, which tends to be fascist as appeared in the issue of constitutional revision. While commending their fights with this complicated issue, by using the critical contextualization approach from the discipline of intercultural theology, this article also shows their limitations in producing solutions to the deadlock between the camp fighting for the constitutional revision and those who resist the proposed amendments. The evangelical figure who uses Kuyperian principles such as the Christian worldview, common grace, and sphere sovereignty yields a response that is arguably more comprehensive and has prospects to be accepted by non-Christians, including the revisionist camp. To Japanese evangelicals who tend to withdraw from socio-political engagements, I argue for utilizing the ecclesiological suggestions of Abraham Kuyper. Particularly, his assertion to keep the church free from the state and Kuyper's distinction of the church's aspects between organism and institution, are beneficial to continue and develop participation in responding to the amendments and other inter-connected nationalism issues.